Exploring Factors that Influence Financial Decision-making Process in Three Selected Public Primary Schools in Kapiri-Mposhi District, Zambia. - Bridget Chirwa; Colious Gondwe; Rosemary Mulenga (International Journal For Multidisciplinary Research, 2026)
This study explored on the factors that influence financial decision-making process in three selected public primary schools in Kapiri-Mposhi District, Zambia. The qualitative methodological approach was used and unstructured interviews guide and FGD were used to collect data. Interpretivism paradigm and a qualitative descriptive design was utilized in this study. The target population of the study included; head teachers, senior teachers and class teacher. Non-probability (homogenous) sampling was used in this study. The sample size consisted of 21 participants broken down as follows: three (3) head teacher teachers, three (3) senior teachers and 5 teacher (five from each school) of the three (3) selected primary schools in Kapiri-Mposhi District. Inductive thematic analysis was employed to analyze data collected. The findings demonstrated that there are various challenges that impede the financial decision-making processes in the selected schools which include; limited funding, lack of financial expertise, maintenance of infrastructure, ineffective financial planning and poor financial record keeping.